Treatment of the humeral shaft fractures - minimally invasive osteosynthesis with bridge plate versus conservative treatment with functional brace: study protocol for a randomised controlled trial - Matsunaga, Fabio T (BioMed Central, 2013)
BACKGROUND: Humeral shaft fractures account for 1 to 3% of all fractures in adults and for 20% of all humeral fractures. Non-operative treatment is still the standard treatment of isolated humeral shaft fractures, although this method can present unsatisfactory results. Surgical treatment is reserved for specific conditions. Modern concepts of internal fixation of long bone shaft fractures advocate relative stabilisation techniques with no harm to fracture zone. Recently described, minimally invasive bridge plate osteosynthesis has been shown to be a secure technique with good results for treating humeral shaft fractures. There is no good quality evidence advocating which method is more effective. This randomised controlled trial will be performed to investigate the effectiveness of surgical treatment of humeral shaft fractures with bridge plating in comparison with conservative treatment with functional brace. METHODS/DESIGN: This randomised clinical trial aims to include 110 patients with humeral shaft fractures who will be allocated after randomisation to one of the two groups: bridge plate or functional brace. Surgical treatment will be performed according to technique described by Livani and Belangero using a narrow DCP plate. Non-operative management will consist of a functional brace for 6 weeks or until fracture consolidation. All patients will be included in the same rehabilitation program and will be followed up for 1 year after intervention. The primary outcome will be the DASH score after 6 months of intervention. As secondary outcomes, we will assess SF-36 questionnaire, treatment complications, Constant score, pain (Visual Analogue Scale) and radiographs. DISCUSSION: According to current evidence shown in a recent systematic review, this study is one of the first randomised controlled trials designed to compare two methods to treat humeral shaft fractures (functional brace and bridge plate surgery). TRIAL REGISTRATION: Current Controlled Trials: ISRCTN24835397